Cell-free chromatin particles released from dying cancer cells activate immune checkpoints in human lymphocytes: implications for cancer therapy - Shabrish, Snehal; Pal, Kavita; Khare, Naveen Kumar; Satsangi, Dharana; Pilankar, Aishwarya; Jadhav, Vishalkumar; Shinde, Sushma; Raphael, Nimisha; Sriram, Gaurav; Lopes, Relestina; Raghuram, Gorantla V.; Tandel, Harshali; et al. (Frontiers in Immunology, 2024)
Immune checkpoint blockade is the exciting breakthrough in cancer, but how immune checkpoints are activated is unknown. We have earlier reported that cell-free chromatin particles (cfChPs) that circulate in blood of cancer patients, or those that are released locally from dying cancer cells, are readily internalized by healthy cells with biological consequences. Here we report that treatment of human lymphocytes with cfChPs isolated from sera of cancer patients led to marked activation of the immune checkpoints PD-1, CTLA-4, LAG-3, NKG2A, and TIM-3. This finding was corroborated in vivo in splenocytes of mice when cfChPs were injected intravenously.Significant upregulation of immune checkpoint was also observed when isolated lymphocytes were exposed to conditioned medium containing cfChPs released from hypoxia-induced dying HeLa cells. Immune checkpoint activation could be downregulated by pre-treating the conditioned media with three different cfChPs deactivating agents. Down-regulation of immune checkpoints by cfChPs deactivating agents may herald a novel form of immunotherapy of cancer.